PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. LAZADA WAREHOUSE - Muhammad Arfian; Hery Wihasnanto (Jurnal Ekonomi dan Industri, 2023)
Purpose to determine the effect of leadership style and organizational culture on employee performance of PT. Lazada Werehouse. This research is included in the category of causal associative research using a quantitative approach. The population in this study were all employees of PT. Lazada Werehouse Warehousing Division, Methods of data analysis using simultaneous and partially linear regression. The results showed that simultaneous and partially leadership style and organizational culture had a positive and significant effect on employee performance of PT. Lazada Werehouse Warehousing Section.